Detectors for space electronics based on the quantum dots and wells - Ustimenko, R. V.; Vinnichenko, M. Ya.; Sarkisyan, H. A.; Hayrapetyan, D. B.; Kazaryan, E. M.
One of the promising areas of research applicable in astrophysics is the study of the properties of quantum dots (QDs) and quantum wells (QWs) in the IR region of the spectrum. The IR region of the spectrum contains a huge amount of astronomical information. Devices based on GaAs/AlGaAs QWs and Ge/Si QDs can serve as detectors and sources of IR radiation. In the current work, the photoluminescence, absorption, and transmission spectra of these nanoheterostructures were obtained in the near, mid, and far IR ranges using Fourier spectroscopy. Thus, the studied optical properties of QWs and QDs make it possible to use these structures in astrophysics as sources and detectors of IR radiation.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture